2000
DOI: 10.1111/j.1469-7793.2000.t01-2-00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the cAMP–protein kinase A pathway facilitates Na+ translocation by the Na+–K+ pump in guinea‐pig ventricular myocytes

Abstract: The effects of the adenylyl cyclase activator forskolin on steady‐state and transient currents generated by the Na+‐K+ pump were studied in guinea‐pig ventricular myocytes by means of whole‐cell voltage clamp at 30 °C. In external solution containing 144 mM Na+ (Na+o) and 10 mM K+ (K+o), steady‐state Na+‐K+ pump current (Ip) activated by 5 mM pipette Na+ (Na+pip) at ‐20 mV was reversibly augmented by forskolin (4 μM) to 133 ± 4 % of the control current (n= 15). The forskolin analogue 1,9‐dideoxyforskolin (10 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 33 publications
7
30
1
Order By: Relevance
“…ϩ -K ϩ pump inhibition mediated by cAMP-dependent pathways in cardiac myocytes was reported in early studies (8,9), but many more recent studies have reported that these pathways mediate pump stimulation either by increasing maximal pump rate or by increasing pump affinity for intracellular Na ϩ (7,(11)(12)(13)(14)(15)(16)30). In our study, forskolin induced glutathionylation of the Na ϩ -K ϩ pump ␤ 1 subunit.…”
Section: Nasupporting
confidence: 52%
See 1 more Smart Citation
“…ϩ -K ϩ pump inhibition mediated by cAMP-dependent pathways in cardiac myocytes was reported in early studies (8,9), but many more recent studies have reported that these pathways mediate pump stimulation either by increasing maximal pump rate or by increasing pump affinity for intracellular Na ϩ (7,(11)(12)(13)(14)(15)(16)30). In our study, forskolin induced glutathionylation of the Na ϩ -K ϩ pump ␤ 1 subunit.…”
Section: Nasupporting
confidence: 52%
“…We have found the ␤ 3 adrenergic receptor mediates stimulation of the Na ϩ -K ϩ pump in cardiac myocytes (5). 5 We, therefore, used forskolin, as have most of the recent studies (7,11,12,15,16).…”
Section: Namentioning
confidence: 99%
“…As noted in an earlier study of guinea-pig ventricular myocytes [25], the time courses of I CFTR activation and I p stimulation by forskolin are strikingly different. This finding suggests differences in the regulation of the two currents by the same intracellular signalling pathway.…”
Section: Introductionmentioning
confidence: 59%
“…Furthermore, I p contributes to the resting membrane potential and the AP form. Recent studies of guinea-pig and rat ventricular myocytes have shown that activation of the cAMP-PKA cascade by either β-adrenergic agonists (noradrenaline, isoprenaline) or the adenylyl cyclase activator forskolin causes an increase in I p [7,18,25]. Stimulation of pump activity by PKA is thought to be important for maintaining the Na + and K + gradients across the sarcolemma since passive Na + and K + fluxes are increased in the presence of β-mimetics.…”
Section: Introductionmentioning
confidence: 99%
“…After a short-term (10 min) treatment of guinea pig myocytes, α-adrenoreceptor (α-AR) agonists increased the I PH without affecting the I PL , and β-adrenoreceptor (β-AR) agonists inhibited the I PL at low intracellular Ca 2+ concentrations ([Ca 2+ ] i ) but did not affect the I PH [5,6,7,8]. However, although some evidence has indicated no effect [9,10] or even inhibition during β-AR activation [5,11,12], most results demonstrate α 1 - or α 2 -isoform stimulation after α-AR or β-AR activation [13,14,15,16,17]. These data are discrepant with the results from Mathias's laboratory, in which the short-term α-AR or β-AR agonist exposure had opposite effects on the I P by affecting specific NKP α-isoforms.…”
Section: Introductionmentioning
confidence: 99%